Improving Learning Outcomes Using the Numbered Heads Together (NHT) Learning Model Assisted by Pop-up Book Media - Fiiki Nur Azizah; Deka Setiawan; Ristiyani, Ristiyani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims tol improve studentl learning outcomesl by using the Numbered Heads Together (NHT) learning model assisted by Pop-up Book media in the Pancasila Education subject in class V of SDN 1 Panjang. This type of research uses a classroom action research method with 24 students as research subjects. There are 2 cycles with 2 meetings in each cycle. Data collection techniques in thisl study include interviews, observations, tests, and documentation. This study uses the expert judgment validation type which includes validation by material experts and media experts to test the truth of the instruments used in the study. The student's score before the study was less than the KKTP, which was 70. After the study was conducted, there wasl an increase in cycle I, namely 75% tol 83.5% in cycle II.